2021
DOI: 10.1609/aaai.v35i7.16734
|View full text |Cite
|
Sign up to set email alerts
|

MARTA: Leveraging Human Rationales for Explainable Text Classification

Abstract: Explainability is a key requirement for text classification in many application domains ranging from sentiment analysis to medical diagnosis or legal reviews. Existing methods often rely on "attention" mechanisms for explaining classification results by estimating the relative importance of input units. However, recent studies have shown that such mechanisms tend to mis-identify irrelevant input units in their explanation. In this work, we propose a hybrid human-AI approach that incorporates human rationales i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…An explanation of a responsive document is one or more text snippets, referred to as rationale in [5], in the responsive document. Explainable predictive coding sets out to build a method to estimate the following probability:…”
Section: Methods For Identifying Responsive Rationalesmentioning
confidence: 99%
See 1 more Smart Citation
“…An explanation of a responsive document is one or more text snippets, referred to as rationale in [5], in the responsive document. Explainable predictive coding sets out to build a method to estimate the following probability:…”
Section: Methods For Identifying Responsive Rationalesmentioning
confidence: 99%
“…Recent research found that a prediction-based approach is often used to identify snippets of text as an explanation for the classification of a document. A text snippet that explains the classification of a document is called a 'rationale' for the document in [4] [5]. From a machine learning perspective, annotated training text snippets provide more effective labeled input due to their targeted evidence relating to the relevance of the decision.…”
Section: Previous Work Research In Explainable Machinementioning
confidence: 99%
“…To construct the topical structure reflecting theme-specific user interests, taxonomies are built upon a foundational seed taxonomy rooted in human knowledge of the application [1,14,26]. An example is the fields of study in the academic domain [46], which embodies researchers' inclination to organize academic concepts and studies.…”
Section: Problem Formulation 21 Concept Definitionmentioning
confidence: 99%
“…A corpus topical taxonomy outlines the latent topic hierarchy within the corpus as a tree structure, where each node is a topic class represented by a cluster of semantically coherent terms describing the topic, as shown in Figure 1. Recent taxonomy construction studies [1,14,26] have effectively reflected user-interested aspects, drawing from a foundational seed taxonomy rooted in human knowledge of the application (e.g., fields of study from Mircosoft Academic [46]). The constructed taxonomy can be subsequently employed to provide additional clues to link queries and documents by discerning their topical relatedness and supplementing the missing contexts.…”
Section: Introductionmentioning
confidence: 99%
“…where α h t ∈ R >0 and β h t ∈ R >0 are the parameters of the distribution at time t. The beta distribution, defined within the interval [0 1] ⊆ R, is well-suited for statistical modeling of human detection reliability and has been previously used in other contexts such as human-aided text classification [32]. For different values of α h t and β h t , we can capture different levels of reliability as shown in Fig 4 on the right (low, mediocre, high).…”
Section: A Human Detection Reliabilitymentioning
confidence: 99%